Pengaruh Strategi Pemasaran terhadap Permintaan dan Penawaran Agregat pada Butik Amadeus di Kota Jambi - Permata Sari, Indah; Sa’adah, Sa’adah; Permata Sari, Nurdiah; Dasdomino Pardede, Ruby; Indah Sari, Pratiwi; Indra Yudha, Redi (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of marketing strategies on aggregate demand and supply at Amadeus Boutique in Jambi City. The marketing strategies studied include product, price, promotion, and distribution dimensions as independent variables, while aggregate demand and supply are the dependent variables. The study population was all Amadeus Boutique customers, with a sample size of 50 respondents determined using a purposive sampling technique. The research instrument was a Likert scale questionnaire, and the data were analyzed using multiple linear regression using SPSS. The results of the analysis showed that marketing strategies simultaneously had a significant effect on aggregate demand and supply with an Fcount value of 19.87 greater than Ftable 2.58 at a significance level of 0.000 < 0.05. Partially, product variables (t-count = 3.42, sig. 0.001) and promotion (t-count = 2.98, sig. 0.004) have a significant effect on demand, while price (t-count = 2.65, sig. 0.011) and distribution (t-count = 2.21, sig. 0.032) are more dominant in contributing to aggregate supply. The coefficient of determination (R²) value is 0.684, which means that 68.4% of the variation in aggregate demand and supply can be explained by marketing strategies, while the remaining 31.6% is influenced by other factors outside this study. This finding confirms that the implementation of appropriate marketing strategies, especially in the product and promotion aspects to increase demand as well as price and distribution to balance supply, can support the sustainability of the competitiveness of Amadeus Boutique in Jambi City.